Effectiveness of adjunctive task-centered case work to pharmacotherapy and motivational enhancement therapy among frequently relapsing patients with alcohol dependence syndrome - Sahoo, Sidhant Kumar; Bhattacharjee, Dipanjan; Khanande, Roshan V; Pachori, Hariom; Khanra, Sourav; Das, Basudeb (Indian journal of psychiatry, 2024)
Background: Individuals experiencing alcohol dependence syndrome (ADS) may struggle with relapse due to various factors, even after receiving successful inpatient treatment. While motivation enhancement therapy (MET) and pharmacotherapy are commonly used interventions for ADS, incorporating task-centered casework (TCP) - a nondirective, goal-oriented, and time-limited approach - may yield promising outcomes. Aim: This study examined the effects of adjunctive TCP in conjunction with pharmacotherapy and MET on frequently relapsing patients with ADS. Materials and Methods: This study utilized a case-control design to evaluate the efficacy of combined therapies (pharmacotherapy, MET, and TCP) on 60 male subjects with a diagnosis of ADS and multiple admissions in a tertiary deaddiction center. The participants were divided equally into experimental and control groups, with the experimental group receiving all three therapies and the control group only receiving pharmacotherapy and MET. Both groups maintained their pharmacotherapy regimens throughout the 2-month study period. Assessments were conducted at baseline and the end of the study using various measures, including social-demographic and clinical data, the SAD-Q, ACQ SF-R, SOCRATES-8A, CIWA-Ar, and WHOQOL-BREF Hindi version. Results: The results of the study indicate that the experimental group exhibited a marked decrease in alcohol cravings, an increased willingness to make positive changes, and overall better treatment outcomes and quality of life compared to the control group. In patients with ADS who underwent treatment with MET, TCP, and pharmacotherapy, it was observed that cravings were a significant predictor of their quality of life and readiness to make changes. Conclusions: TCP can be complemented with existing addiction therapies in the treatment of addiction because it has additional advantages in the form of nondirectiveness, goal orientation, time-limitedness, and collaboration between the therapist and the patient. ADS patients can benefit from this therapy by discovering their inert potential and identifying their shortcomings.